Fraud Dan Corporate Governance: Pemetaan Tren Penelitian Dan Wawasan Teoritis Dengan Analisis Bibliometrik - Kamilah, Raida Shafa (Politeknik Negeri Ambon, 2025)
This study uses bibliometric analysis to analyze trends and patterns in academic literature on fraud and corporate governance. Based on 302 articles from the Scopus database between 2000 and 2024, it explores publication trends, identifies key topics, and maps the academic network in this field. The results show a significant increase in publications on these topics, driven by the global financial crisis and corporate scandals. The Journal of Business Ethics is the leading journal in publishing research on corporate governance and fraud prevention, while the United States is the top contributor with significant influence. This study provides a reference for future research on fraud and corporate governance.